The Mughals and the Sufis : Islam and political imagination in India, 1500-1750 - Alam, Muzaffar, 1947- (State University of New York Press, 2021)
"Examines the relationship between Mughal political culture and the two dominant strains of Islam's Sufi traditions in South Asia: one centred around orthodoxy, the other focusing on a more accommodating and mystical spirituality"-- Provided by publisher.
Keywords: Sufism -- India -- History.; Islam and politics -- India.; Islam and state -- India.; Mughal Empire -- Religion.; Mughal Empire -- Politics and government.; India -- Politics and government -- 997-1765.; Soufisme -- Inde -- Histoire.; Islam et État -- Inde.; Empire moghol -- Religion.; Inde -- Politique et gouvernement -- 997-1765.; HISTORY / Asia / India & South Asia.; Islam and politics; Islam and state; Politics and government; Religion; Sufism; India; India -- Mogul Empire; 997-1765; History